2016
DOI: 10.1002/pola.28108
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled synthesis of soluble-conjugated microporous polymer nanoparticles through sonogashira polycondensation in confined nanoreactors

Abstract: Soluble conjugated polymeric nanoparticles were synthesized through Sonogashira polycondensation between different combinations of multifunctional alkynes and aryl halides in structurally well‐defined mesoporous reactors. The growth of the polymeric nanoparticles was controlled by the spatial confinement of the nanoreactors, giving conjugated polymeric nanoparticles with narrow size distribution centered at 5 nm. All the obtained polymers are freely soluble in common solvents and can be fabricated into thin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In 2016, Hu and co‐workers reported that soluble conjugated polymeric nanoparticles were synthesized through Sonogashira polycondensation between different combinations of multifunctional alkynes and aryl halides in structurally well‐defined mesoporous reactors. The growth of the polymeric nanoparticles was controlled by the spatial confinement of the nanoreactors, giving conjugated polymeric nanoparticles with narrow size distribution centered at 5 nm . The machine‐shaping of CMPs is feasible by adjusting the solubility of CMPs in the solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Hu and co‐workers reported that soluble conjugated polymeric nanoparticles were synthesized through Sonogashira polycondensation between different combinations of multifunctional alkynes and aryl halides in structurally well‐defined mesoporous reactors. The growth of the polymeric nanoparticles was controlled by the spatial confinement of the nanoreactors, giving conjugated polymeric nanoparticles with narrow size distribution centered at 5 nm . The machine‐shaping of CMPs is feasible by adjusting the solubility of CMPs in the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the polymeric nanoparticles was controlled by the spatial confinement of the nanoreactors, giving conjugated polymeric nanoparticles with narrow size distribution centered at 5 nm. [32] The machineshaping of CMPs is feasible by adjusting the solubility of CMPs in the solvent. Except for these two investigations, the study on synthesis of soluble CMPs has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of aryl or vinyl halides (or triflate) with terminal alkynes catalyzed by palladium, commonly termed Sonogashira cross‐coupling reactions, has been recognized as one of the most important sp 2 –sp carbon–carbon bond formation reactions in organic synthesis . The resulting internal alkynes or enynes are important intermediates for pharmaceuticals, natural products, biologically active molecules, conducting polymers and optical and liquid‐crystal materials . The most commonly utilized catalytic systems for these reactions include phosphine‐ligated palladium catalysts together with CuI as a co‐catalyst under degassed conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in most cases, the applicability of the boronic acid systems was restricted due to their limited solubility in aqueous solutions. Recently, our group reported a new method to synthesize sizecontrolled conjugated microporous polymers (CMPs) through polycondensations 25,26 in conned nanoreactor, where the catalysts (palladium nanoparticles) were embedded in mesoporous supports, namely, silica-supported carbon nanomembranes (SS-CNMs). CMPs, a class of amorphous materials possessing three-dimensional networks with their building blocks linked in a p-conjugated fashion, have emerged as an important material platform since 2007.…”
Section: 15mentioning
confidence: 99%